Responsibility centres in the system of controlling - Tamulevičienė, Daiva (Buhalterinės apskaitos teorija ir praktika, 2014)
Controlling is the new concept of modern management based on planning, control, accountability, and coordinate and consultative activity. One of the essential conditions of the installation of controlling is decentralization of management. The information in the system of controlling is accumulated and analysed not at the level of the whole company, but at the separate segments called as responsibility centres. The aim of the article is to examine the significance of the responsibility centres in the system of controlling and to propose the methodology of responsibility centres establishment and evaluation of theirs activity.The responsibility centre might be a division of the company or some segment of activity or geography. Depending on what responsibility centres would be created in the company, that would have an effect on efficiency of the controlling system‘s behaviour. Although there exist many different features of the classification of responsibility centres, it is appropriate, in the companies‘ practice, to make responsibility centres in accordance with the fields of activity: cost, revenue, profit and investment centres. It is appropriate to make and install the system of responsibility centres and internal reporting by suggested sequence of four stages: organizational structure diagnostics; establishment of responsibility centres; establishment of internal reporting by the responsibility centres and establishment of the system of evaluation of the responsibility centres activity and motivation of employees.The purpose of responsibility centres and installation of responsibility accounting in the controlling system is to ensure an efficient behaviour of the organization and the maximization of its results both in short-term and in long-term perspective. The only way to reach the purpose is by evaluating the input of each responsibility centre‘s to the overall result. The controlling service‘s task is to solve all the problems that occur in practice when establishing the responsibility centres and the reporting of responsibility centres and to select such indicators of the evaluation of each centre that would reflect the connection of activity of corresponding centre‘s employees and their achievements to the goals of organization in the best possible way.
Keywords: controlling; responsibility centres; responsibility accounting; evaluation of responsibility centre performance